Peran Media Sosial Dalam Pemberdayaan Masyarakat Pada Konteks Politik - Rifki, Muhammad; Safira, Zahra; Ahmad, Fadiel; Maulana Setiawan, Mochammad Naufal; Mubaraok, Said; Nadaraning, Eilde; Pratiwi, Sandra (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2024)
The development of social media has changed the political landscape and public participation in the political context has become more dynamic. In this context, this research aims to explore the role of social media in empowering society in the political realm in Indonesia. Through a qualitative approach and literature analysis, this study highlights how social media provides wider access for individuals to participate in the political process, influence public opinion, and mobilize political support. Apart from that, this research also explores the positive and negative impacts of the role of social media in strengthening people's political participation and highlights the challenges and opportunities faced in using social media for political purposes. It is hoped that the results of this research will provide deeper insight into how social media can be an effective tool in increasing community political participation and supporting the democratization process in Indonesia.